1997
DOI: 10.1002/chin.199715156
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis, Structural Analysis and Pharmacological Effects of N2‐ Substituted 3,4‐Dihydrobenzo(h)quinolin‐2‐amines.

Abstract: Synthesis, Structural Analysis and Pharmacological Effects of N2-Substituted 3,4-Dihydrobenzo(h)quinolin-2-amines.-The title compound (VIa) displays antiarrhythmic effect at the papillary muscle of guinea pigs and reduces moderately the heart rate in rats. -(WENDELIN, W.; KEIMELMAYR, H.; GOESSNITZER, E.; ABOU EL ELLA, D.; Pharmazie 51 (1996) 11, 816-822; Inst. Pharm. Chem., Karl-Franzens-Univ., A-8010 Graz, Austria; EN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…IR spectra for the compounds as KBr tablets were recorded on a Pye-Unicam SP3-300 instrument. 1 H and 13 C NMR spectra were taken on a Varian Mercury 400 (400 and 100 MHz) spectrometer using DMSO-d 6 and with TMS as internal standard and UV spectra on a Specord M400 spectrophotometer. Monitoring of the reaction course and purity of the compounds obtained was carried out by TLC on Silufol UV-254 plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectra for the compounds as KBr tablets were recorded on a Pye-Unicam SP3-300 instrument. 1 H and 13 C NMR spectra were taken on a Varian Mercury 400 (400 and 100 MHz) spectrometer using DMSO-d 6 and with TMS as internal standard and UV spectra on a Specord M400 spectrophotometer. Monitoring of the reaction course and purity of the compounds obtained was carried out by TLC on Silufol UV-254 plates.…”
Section: Methodsmentioning
confidence: 99%
“…However, by contrast to 5-oxoisoquino [2,3-a]quinazolines, the properties of the latter were not studied. The already existing data for the biological activity of isoquinoquinazolines [5,6] and 4-arylquinazolines condensed along the a edge [7][8][9] points to the potential of such an investigation.…”
mentioning
confidence: 99%
“…Structures in which imidazole nucleus is annulated with a benzazepine platform have a powerful biomedical potential. In particular, substances that exhibit antibacterial [7] and antihypertensive [8] activity were found in a number of derivatives of imidazobenzazepines. They are effective antagonists of histamine (H1) [9] and serotonin (5‐HT2A) [10] receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of literature sources has shown that among the methods of the synthesis of imidazobenzazepine structures the most common are various intramolecular cyclizations of functionalized benzazepine derivatives, [7,8,15] which often require the use of hard-to-reach reagents, are not always characterized by high selectivity and yields, and in many cases are characterized by the absence of functional groups in the target compounds. That is why the development of new methods for the preparation of imidazobenzazepine scaffolds ChemistrySelect www.chemistryselect.org with incorporated functional fragments, including pharmacophore ones, is an urgent synthetic problem.…”
Section: Introductionmentioning
confidence: 99%
“…According to the MDDR database [2], the isoquinol-1-one structural fragment is present in three medical products on the pharmaceutical market: Draquinolol, Tilisolol, and Palonosetron. Derivatives of 3-aminoisoquinol-1-one have also been patented: A non-narcotic analgesic [3] and an inhibitor of poly(ADP-riboso)synthetase [4].Data on the properties of derivatives of the isoquino[3,2-b]quinazoline series first appeared in the middle of the last century: The cyanoethylation and oxidation of 5,13-dihydro-11H-isoquino[3,2-b]quinazolin-11-one (1) were mentioned in [5], and high antifungal and antibacterial activity was discovered in the case of 6,11-dihydro-13H-isoquino[3,2-b]quinazolin-13-one [6]. The presence of a secondary enamine fragment in the molecule of isoquino[3,2-b]quinazolin-11-one 1 is promising in respect of further modification of the structure, and this makes it possible to expect that the high activity and chemical selectivity of this group will appear in reactions with electrophilic reagents.…”
mentioning
confidence: 99%